Sea cucumber (Acaudina leucoprocta) peptides extended the lifespan and enhanced antioxidant capacity via DAF-16/DAF-2/SOD-3/OLD-1/PEPT-1 in Caenorhabditis elegans - Wu, Yue; Yang, Jingjuan; Xu, Chengmei; Li, Qiuqi; Ma, Yage; Zhao, Shenglan; Zhuang, Jiachen; Shen, Fei; Wang, Qianqian; Feng, Fengqin; Zhang, Xi (Frontiers in Nutrition, 2022)
The sea cucumber peptides (SCPs) from Acaudina leucoprocta were derived from the patented bio-enzyme digestion technology and the molecular weight of obtained SCPs was less than 10 kDa. In this study, we investigated the possible anti-aging effects of SCPs on the model of Caenorhabditis elegans and the underlying mechanisms. SCPs extend the average lifespan of nematodes by 31.46%. SCPs enhance the anti-stress capacity of C. elegans by improving heat resistance and mobility, Also, the accumulated potential oxidative stress inducers like lipofuscin and reactive oxygen species (ROS) were reduced to 40.84% and 71.43%. In addition, SCPs can increase the antioxidant capacity in nematodes by enhancing the activity of SOD and CAT and reducing MDA accumulation in nematodes to 32.44%. Mechanistically, SCPs could mediate DAF-16/DAF-2/SOD-3/OLD-1/PEPT-1 axis to improve antioxidant capacity and extend lifespan in nematodes. Taken together, these findings provide a direction for the anti-aging effects of sea cucumber peptides and new insights into the further purifications of SCPs and future research on aging.